Association of changes in red meat consumption with total and cause specific mortality among US women and men: two prospective cohort studies - Zheng, Yan; Li, Yanping; Satija, Ambika; Pan, An; Sotos-Prieto, Mercedes; Rimm, Eric; Willett, Walter C; Hu, Frank B (BMJ (Online), 2019)
AbstractObjectiveTo evaluate the association of changes in red meat consumption with total and cause specific mortality in women and men.DesignTwo prospective cohort studies with repeated measures of diet and lifestyle factors.SettingNurses’ Health Study and the Health Professionals Follow-up Study, United States.Participants53 553 women and 27 916 men without cardiovascular disease or cancer at baseline.Main outcome measureDeath confirmed by state vital statistics records, the national death index, or reported by families and the postal system.Results14 019 deaths occurred during 1.2 million person years of follow-up. Increases in red meat consumption over eight years were associated with a higher mortality risk in the subsequent eight years among women and men (both P for trend<0.05, P for heterogeneity=0.97). An increase in total red meat consumption of at least half a serving per day was associated with a 10% higher mortality risk (pooled hazard ratio 1.10, 95% confidence interval 1.04 to 1.17). For processed and unprocessed red meat consumption, an increase of at least half a serving per day was associated with a 13% higher mortality risk (1.13, 1.04 to 1.23) and a 9% higher mortality risk (1.09, 1.02 to 1.17), respectively. A decrease in consumption of processed or unprocessed red meat of at least half a serving per day was not associated with mortality risk. The association between increased red meat consumption and mortality risk was consistent across subgroups defined by age, physical activity, dietary quality, smoking status, or alcohol consumption.ConclusionIncreases in red meat consumption, especially processed meat, were associated with higher overall mortality rates.